Rigidotubus tephroleucus gen. et sp. nov. (Cystostereaceae, Agaricales) evidenced by morphological characters and phylogenetic analyses - Song, Jie; Xing, Jia-Hui; Ji, Xing; Sun, Yi-Fei; Cui, Bao-Kai; Dai, Yu-Cheng (Phytotaxa, 2018)
A new poroid wood-inhabiting fungal genus, Rigidotubus, is proposed to accommodate R. tephroleucus sp. nov. based on morphological characters and molecular evidence. The genus is characterized by tough and poroid basidiomata, white to grayish white pore surface, white sterile margin, a monomitic hyphal system with clamped generative hyphae, ovoid to ellipsoid basidiospores negative in Melzer’s reagent and Cotton Blue. The phylogenetic analyses inferred from the internal transcribed spacer (ITS) and nuclear large subunit (28S) ribosomal RNA gene regions confirmed that Rigidotubus belongs to Cystostereaceae in Agaricales. A key to the accepted genera of Cystostereaceae is provided.